Statistical optimization of zinc removal using activated carbon and magnetic biochar - Mujawar, Mubarak; Alicia, R.; Sahu, J.; Haslija, A.; Tan, J. (2014)
Due to the increasing of industrial wastage, content of metal in waste water has increased drastically. The effectiveness of Zn 2+ removal from aqueous solution by different adsorbents was experimentally studied. The effect of the process parameters such as pH, adsorbent dosage, agitation speed and contact time were examined whereby the experimental design of the investigation was conducted using Design Expert® Version 6.08. The statistical analysis revealed that that optimum condition for magnetic bochar and activated cabon was at pH 10, dosage 0.09 g, agitation speed and time of 120 rpm and 60 min respectively. It is found that the removal efficiency of Zn 2+ for an initial concentration of 10 mg/l using magnetic biochar was 95% and using activated carbon was 65%. Based on the results, it was proven that magnetic biochar emerges as the most promising adsorbent in the removal of Zn 2+ compared to activated carbon.